Analysis of Law Enforcement Against Terrorism and Human Rights Protection in Indonesian Legal Politics - Ronal Balderima; Andry Dwiarnanto (Mandalika Institute, 2026)
Terrorism is an extraordinary crime that threatens national security, state sovereignty, and the human rights of the people. In the context of Indonesian legal politics, law enforcement efforts against criminal acts of terrorism continue to develop through the formation of regulations and strengthening of law enforcement officers. However, the implementation of terrorism eradication often raises debates regarding the protection of human rights, especially regarding the right to freedom, the right to justice, and protection against repressive actions by the authorities. This study aims to analyze law enforcement against terrorism from the perspective of Indonesian legal politics and examine the extent to which human rights protection is implemented in the process. The research method used is normative legal research with a legislative approach and a conceptual approach. Data were obtained through a literature review of relevant laws and regulations, journals, and legal literature. The results show that the legal policy of terrorism eradication in Indonesia is directed at strengthening national security through a preventive and repressive approach, as stipulated in Law Number 5 of 2018 concerning the Eradication of Criminal Acts of Terrorism. However, the implementation of law enforcement still faces challenges in the form of potential human rights violations during arrests, detentions, and actions by security forces. Therefore, a balance is needed between state security interests and human rights protection to ensure that law enforcement against terrorism remains compliant with the principles of the rule of law and democracy.